Exploring the impact of culture on the formation of consumer trust in Internet shopping - Ilagan, Sheila V. (ProQuest LLC, 2009)
This study investigated cultural differences in consumers' perceptions of the company, general perceptions of privacy and security of the Web, perceptions of the risks and benefits of online shopping and how these perceptions affect consumer trust in Internet shopping. It also examined the effect of individual characteristics on consumers' decision to buy online and the factors that predict trust in online shopping. Respondents from individualistic and collectivistic nations significantly differ in their perceptions of the Internet merchant's reputation and the risks of online shopping. Respondents from collectivistic nations reported a more positive perception of reputation and a higher level of perceived risks. Attitude towards using a virtual store and propensity to trust have a moderating effect on the relationship between trust in Internet shopping and the respondents' perceptions of the antecedents to trust. Perceived risks, perceived security protection, perceived reputation, and perceived size were the significant predictors of consumer trust in Internet shopping. Across all cultural differences and differences in attitude and propensity to trust, perceived risks was the single most significant predictor. Among respondents from individualistic nations and those with a positive attitude towards using a virtual store and a high propensity to trust, perceived reputation was also a significant predictor of their decision to buy online. Perceived security protection also affects trust of respondents from collectivistic countries and those with a negative attitude towards using a virtual store while security protection, size, and reputation were the other factors considered by respondents with low propensity to trust when deciding to buy online.--Abstract.